2022
DOI: 10.3389/fimmu.2022.832924
|View full text |Cite
|
Sign up to set email alerts
|

Local and Systemic Immunity Are Impaired in End-Stage-Renal-Disease Patients Treated With Hemodialysis, Peritoneal Dialysis and Kidney Transplant Recipients Immunized With BNT162b2 Pfizer-BioNTech SARS-CoV-2 Vaccine

Abstract: Vaccination against COVID-19 in patients with end-stage renal disease (ESRD) on replacement therapy and kidney transplant recipients (KTRs) is particularly important due to the high mortality rate. Here, we tested the local and systemic immunity to the novel Pfizer BioNTech (BNT162b2) messenger RNA (mRNA) in ESRD, KTR patients, and healthy individuals (150 subjects). The ESRD group was divided into: hemodialysis (HD) and peritoneal dialysis (PD). We investigated the local and systemic immunity based on anti-N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Terminal kidney failure, immunosuppressive therapy, and concomitant diseases make the population of HD/KTRs especially vulnerable to severe COVID-19. HD patients develop an impaired cellular and humoral response to COVID-19 vaccination compared to the general population [ 5 ]. KTRs show a preserved symptom-dependent humoral response to SARS-CoV-2 infection [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terminal kidney failure, immunosuppressive therapy, and concomitant diseases make the population of HD/KTRs especially vulnerable to severe COVID-19. HD patients develop an impaired cellular and humoral response to COVID-19 vaccination compared to the general population [ 5 ]. KTRs show a preserved symptom-dependent humoral response to SARS-CoV-2 infection [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the response to vaccination in HD patients and KTRs is much lower than in the general population [ 5 ]. For the aforementioned reasons, using effective drugs against COVID-19 in these patient groups is essential.…”
Section: Introductionmentioning
confidence: 99%
“…These studies used various vaccine platforms (including mRNA, inactivated, viral vector and heterologous vaccines) as well as different units of measurements. Table 2 summarizes the comparison of IgG levels between HD and control groups following COVID-19 vaccination obtained from the 30 studies [ 16 20 , 22 25 , 27 29 , 31 , 33 36 , 38 40 , 43 , 44 , 46 48 , 51 , 53 , 54 , 59 ]. Overall, twenty-nine studies demonstrated lower IgG levels after COVID-19 vaccination in HD patients compared to healthy controls, whereas only one study by Panizo showed a contrary finding [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study reported that 35% of the studied dialysis patients (130 HD patients and 13 PD patients) had low or undetectable levels of IgG antibodies against SARS-CoV-2 Spike (S) protein following two doses of the BNT162b2 or mRNA-1273 vaccines [63]. Despite this overall reduced response to vaccination, it should be noted that individual studies as well as a meta-analysis have demonstrated stronger humoral responses to vaccination in PD patients compared to HD patients [64,65]. For example, Tylicki et al's study showed that PD patients (n = 21) had more robust anti-S IgG antibody titers following both the first (p = 0.034) and second (p = 0.008) doses of the BNT162b2 vaccine compared to HD patients (n = 35) [66].…”
Section: Comparison To Hemodialysismentioning
confidence: 99%